The Development of E-Handout Teaching Materials for the Sub-Concept of Structure and Function of Tissues in Plants - Anisa Rahmatina; Noorhidayati Noorhidayati; Aulia Ajizah (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
Learning in the 21st century is supported by mastery of technology. The utilization of technology in education can be implemented in the use of electronic teaching materials, one of which is E-Handout. The purpose of this study was to describe the needs analysis, validity and practicality of the results of the Development of E-Handout Teaching Materials for the Sub-Concept of Structure and Function of Tissues In Plants. This research is categorized as research and development (R&D) based on the 4D model. Data collection used teacher and students needs instruments, validity and practicality questionnaires. The research subjects were 3 experts and 12 students of class XI MIPA at SMA Negeri 1 Alalak. The results showed that first, the results of the needs analysis were "good" (77.83), meaning that E-Handout teaching materials need to be developed on the Sub-Concept of Structure and Function of Tissues in Plants. Second, E-Handout have a validity of "very valid" (88.45), meaning that E-Handout is very valid and in accordance with learning objectives, language, format and media. Third, the practicality results are "very good" (91.88), meaning that the E-Handout is very practical and easy to read by students. This shows that the E-Handout developed is valid and practical so that it can be used as teaching material as needed. The implication of the research results is that students can learn independently anytime and anywhere using E-Handout via laptop or smartphone.